Carbon budgets are not enough – the case for transition milestones - Lilliestam, Johan; Sharpe, Simon; Worthington, Bryony (2025)
2 SUMMARY • Carbon budgets can support emissions reduction by focusing political attention, providing a framework for planning, and enabling accountability over time. These are important advantages compared to ad hoc policymaking without a governance framework. • However, there are risks in making near-term (as well as long-term) emissions reduction the measure of success in a governance framework. Not all actions that reduce emissions in the short-term make progress towards the elimination of emissions in the long-term. Governments that focus on reducing emissions by increasing the efficiency of fossil fuel systems and deploying lower emission technologies risk wasting time, wasting investment, and storing up problems for the future. • Eliminating anthropogenic emissions is the only plausible way to reduce climate risk, and only the development of zero emission systems can achieve that outcome. Making this the measure of success in a governance framework would strongly align short-term focus with long-term goals. We propose transition milestones for this purpose: interim targets for the market share of zero emission solutions in each of the greenhouse-gas emitting sectors, accompanied by qualitative descriptions of conditions necessary to complete each stage of the transition. • Transition milestones can be set to reflect a country’s circumstances, strengths, and strategic objectives. Since most countries account for a very small share of global emissions, influencing global economic change is at least as important as eliminating national emissions, for reducing climate change risks. • Transition milestones have their own limitations and risks, and will not direct attention towards all opportunities for useful emissions reduction. There may be advantages in using a combined framework, with transition milestones alongside carbon budgets.<br